An Analysis of Influencing Factors on Poverty in Sustainability Development Framework: A Case in Deli Serdang Regency, Indonesia - Tarmizi, Hasan Basri (Journal of Economics and Behavioral Studies, 2014)
This research aims to analyze some factors influencing poverty in Deli Serdang regency. The method used in this research is the quantitative method with the multiple linear regression analysis. There are five variables; Gross Domestic Product, population, market share of industrial sector, inflation and education are used as independent variables. The number of poverty population is dependent variable with data series taken from the year 1985 up to 2011. The result of this research simultaneously implies that the GDP, population, market share of industrial sector, inflation and education are influencing the number of population in poverty, while the GDP and population influence partially the same population in Deli Serdang regency.